Comparison of the Effectiveness of Emotionally Focused Couple Therapy and Schema Therapy on Emotional Exhaustion and Attachment Styles in Women with Marital Conflict - Shahbaz, Zahra; Barati, Hadi (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to compare the effectiveness of Emotionally Focused Couple Therapy (EFCT) and Schema Therapy on emotional exhaustion and attachment styles (secure, avoidant, and ambivalent) in women experiencing marital conflict. Methods and Materials: This study employed a quasi-experimental design with three groups (two experimental groups and one control group) and three measurement stages (pretest, posttest, and 45-day follow-up). The statistical population consisted of women with marital conflict who referred to family and couple counseling centers in Isfahan during spring 2025. Forty-five participants were selected using purposive sampling based on inclusion criteria and randomly assigned to an Emotionally Focused Couple Therapy group, a Schema Therapy group, or a control group (n = 15 per group). The EFCT intervention was conducted in nine 90-minute group sessions held twice weekly, whereas Schema Therapy was delivered in twelve 90-minute group sessions twice weekly. The control group received no intervention. Data were collected using the Emotional Exhaustion Questionnaire and the Attachment Styles Questionnaire and analyzed using repeated measures analysis of variance with Greenhouse–Geisser correction and Bonferroni post hoc comparisons in SPSS-26. Findings: Repeated measures analysis indicated significant between-group differences for emotional exhaustion, secure attachment, avoidant attachment, and ambivalent attachment (p < .001). Significant main effects of time were observed across all variables (p < .001), demonstrating meaningful change across pretest, posttest, and follow-up stages. Significant time × group interaction effects confirmed differential change patterns among groups (p < .001). Post hoc comparisons showed that both EFCT and Schema Therapy significantly reduced emotional exhaustion and insecure attachment styles while increasing secure attachment compared with the control group at posttest and follow-up (p < .05). EFCT demonstrated significantly greater effectiveness than Schema Therapy only in reducing emotional exhaustion at posttest and follow-up (p < .05), whereas no significant differences were found between the two interventions in attachment style outcomes (p > .05). Conclusion: Both Emotionally Focused Couple Therapy and Schema Therapy were effective interventions for reducing emotional exhaustion and improving attachment security among women experiencing marital conflict, with treatment effects maintained at follow-up; however, EFCT showed superior effectiveness in alleviating emotional exhaustion, suggesting its particular suitability for couples presenting with relational burnout and affective depletion.